2015
DOI: 10.1111/jnu.12173
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Magnet Status, Unit Work Environment, and Pressure Ulcers

Abstract: Investment in the nurse work environments at both the hospital level and unit level has the potential to reduce HAPUs; and additional to hospital-level initiatives (e.g., Magnet recognition program), efforts targeting on-unit work environments deserve more attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 38 publications
2
49
0
3
Order By: Relevance
“…Regarding perception of the work environment, the percentage of nurses who rated their centre as a ‘favourable practice environment’ rose from 13.9% to 20% and from 2.31 to 2.44 in the PES‐NWI average global score. These results are within the range of average scores (2.30–3.07) obtained in other studies (Swiger et al, ), albeit far from the results presented for centres designated magnet hospitals (2.92–3.00) (Kutney‐Lee et al, ; Ma & Park, ). With respect to the increase in job satisfaction, nurses in 2012–2014 reported feeling more satisfied with independence at work and professional status.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Regarding perception of the work environment, the percentage of nurses who rated their centre as a ‘favourable practice environment’ rose from 13.9% to 20% and from 2.31 to 2.44 in the PES‐NWI average global score. These results are within the range of average scores (2.30–3.07) obtained in other studies (Swiger et al, ), albeit far from the results presented for centres designated magnet hospitals (2.92–3.00) (Kutney‐Lee et al, ; Ma & Park, ). With respect to the increase in job satisfaction, nurses in 2012–2014 reported feeling more satisfied with independence at work and professional status.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, reduction in the nurse–patient ratio only produces better health outcomes in healthy practice environments (Aiken, Cimiotti, et al, ; Aiken, Sloane, et al, ). This has been confirmed recently, showing pressure ulcers were significantly less likely to occur in nursing units in Magnet hospitals or in favourable work environments (Ma & Park, ).…”
Section: Introductionsupporting
confidence: 64%
“…Furthermore, positive work environments have been associated with nurse sensitive patient outcomes. Recent studies have found that better nurse work environments are associated with lower hospital acquired pressure ulcers, 10 30 day readmissions in Medicare patients undergoing surgery, 11 and 30 day surgical mortality and failure to rescue. 12 Likewise, patients in hospitals gave the hospitals a higher overall rating if they had a better nurse work environment, and were more likely to recommend the hospital and reported more positive care experiences with nurse communication.…”
Section: Introductionmentioning
confidence: 99%
“…Nurse practice environment is the context in which nurses complete patient care activities. It has been found to be associated with patient outcomes, such as mortality and pressure injuries (Aiken, Clarke, Sloane, Lake, & Cheney, ; Ma & Park, ). According to Donabedian's structure‐process‐outcome model, the nurse practice environment also can influence the process of care, namely, missed nursing care in this study.…”
mentioning
confidence: 99%